Physical Fitness, Exercise Behaviors, and Sense of Self-Efficacy Among College Students: A Descriptive Correlational Study - Han, Shan-shan; Li, Bo; Wang, Guang-xu; Ke, You-zhi; Meng, Shu-qiao; Li, Ya-xing; Cui, Zhong-lei; Tong, Wen-xia (Frontiers in Psychology, 2022)
Background: Self-efficacy is an important component of the mental well-being of college students. This study aimed to evaluate the development and the correlation between physical fitness（PF）, exercise behavior, and self-efficacy in college students. To examine whether physical fitness in individual college students can predict self-efficacy, and whether exercise behavior mediates this relationship. Methods: This was an observational study of 1923 randomly selected college students (50.5% girl). Measures included the Physical Activity Rating Scale, the Self-Efficacy Scale, and physical fitness testing. Results: Self-efficacy was weakly correlated to both physical fitness (r=0.240) and exercise behavior (r=0.248). In regression analysis, physical fitness explained 24.7% of the variance in self-efficacy, increasing to 29.4% when exercise behavior was considered. Therefore, the predictive effect of physical fitness on self-efficacy is partially realized through healthy exercise behavior. Conclusion: Physical fitness can predict self-efficacy among college students, with exercise behavior being an important mediation of this relationship. Strategies to improve positive exercise behaviors and physical fitness could improve students’ self-efficacy and overall mental health.